Responses of persimmon (Diospyros kaki) fruits to different fruit coatings during postharvest storage at ambient temperature - Khan, Muhammad Jalal; Ayub, Qasim; Hussain, Ijaz; Mehmood, Abid; Arif, Nida; Mehmood, Saad; Shehzad, Qammer; Khalid, Sarmad; Naveed Ul Haq (Journal of Pure and Applied Agriculture, 2023)
Horticultural crops are a key source of food and nutrition for human beings since the beginning of time. Storage of horticultural crops after harvesting and marketing has numerous distinctive characteristics due to the unique properties of the crops. Due to high perishability, seasonal dependence and bulky harvest in a season, horticultural crops require special care and attention, for delaying ripening and senescence during the transportation of product to distinct markets require proper skills. Edible coating have been long used to preserve the quality of horticultural products and many studies have proved the beneficial effects of these coating, so the current study is carried out to investigate the effects of different edible